TRAINING TO THE FIELD OF COLLECTIVE HEALTH IN A NURSING UNDERGRADUATION COURSE FROM THE POINT OF VIEW OF THE EGRESSES (Fiep Bulletin - online, 2014)
We highlight the evaluation of the graduation process in the perspective of the egresses, who are challenged in their routine to confront the competences developed during the course, with the ones required in professional exercise. We aimed to recognize the walked path; the fields of actuation; diagnose about the process of training to public health. Quantitative descriptive exploratory study, with data obtained in structured interviews with egresses of under graduation in nursing graduated since the Pedagogical Political Project implemented in 2003 carried out between May and August 2012. There were found 91.87% of the subjects of female gender, average ages between 27 – 38 years old, who evaluated positively the received training to actuate in public health. The evaluated items: offered content; employed teaching methodology; the experienced evaluations; lived professor-student relationship; established theory and practice relationship; and the concept to training, having as a base the professional practice indicated high-frequency between concepts excellent and good in every item. They have attributed excellent concept to the training 42.2%, and good 39.9% of the egresses. They comprehended pertinent the received training by characterization of the public health area as fundamental in their professional acting. We hope the revealed data to contribute to the training offered during the course.
Keywords: Superior Education; Egresses; Nursing